2009
DOI: 10.1017/s0022215109992325
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of computer-assisted surgery in patients with chronic rhinosinusitis

Abstract: Objective: To compare the complication rates and outcome of computer-assisted versus non-computer-assisted functional endoscopic sinus surgery.Methods: We reviewed retrospectively the medical records of 276 patients who had undergone sinus surgery for chronic rhinosinusitis with (n ¼ 108) or without (n ¼ 168) computer assistance, from 1996 to 2004, to determine the incidence of complications and need for revision surgery.Results: The incidence of complications was 6.5 per cent in the computer-assisted group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 22 publications
1
51
0
1
Order By: Relevance
“…1209 Most authors have not detected differences in complications with IGS. 1211,1212 A 2013 systematic review, by Ramakrishan et al 1212 concluded that the peer-reviewed literature does not support conclusions that IGS reduces complications and improves clinical outcomes. These authors recommend IGS as an option, because the consensus of practicing surgeons and expert opinion confirm the utility and acceptance of IGS technology.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
“…1209 Most authors have not detected differences in complications with IGS. 1211,1212 A 2013 systematic review, by Ramakrishan et al 1212 concluded that the peer-reviewed literature does not support conclusions that IGS reduces complications and improves clinical outcomes. These authors recommend IGS as an option, because the consensus of practicing surgeons and expert opinion confirm the utility and acceptance of IGS technology.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
“…Many have found no significant difference in outcome measures. 6,7 However, some have reported reductions in the incidence of major complications when computer assistance has been used. 8 The benefit of computer assistance during ESS is still undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeries were less frequently interrupted due to bleedings, although the total blood loss in the use of navigation was higher [565]. Other authors did not notice any effect on intraoperative complications or the (subjective or objective) result of the operation [15], [563], [564], [566], [567], [568], [569]. Complications were also caused by navigation- in some cases e.g.…”
Section: Structural Qualitymentioning
confidence: 99%
“…In regard of these facts, the surgeon must be advised to control the system repeatedly during the operation by means of identified landmarks [571], [572]. Generally a divergence of 1-3 mm in routine surgery can be expected [559], [560], [567], [570], [572], [573], [574]. …”
Section: Structural Qualitymentioning
confidence: 99%